2012
DOI: 10.5812/jjm.4583
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Bacteria Isolated From Endotracheal Tubes of Patients in Golestan Hospital, Ahvaz, Iran, and Determination of Their Antibiotic Susceptibility Patterns

Abstract: The findings of this study reflect the emergence of antibiotic resistant infections in our hospital wards especially ICU and NICU. This provides the useful information for HAI surveillance in teaching hospitals to control and manage nosocomial infections caused by highly resistant organisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 18 publications
3
15
0
Order By: Relevance
“…The results showed that 67.3% of E. coli isolates were resistant to Nalidixic acid (25). The similarity between this study and the present study was that in the current study was found to be most resistance to Nalidixic acid (59.7%).…”
Section: Discussionsupporting
confidence: 83%
“…The results showed that 67.3% of E. coli isolates were resistant to Nalidixic acid (25). The similarity between this study and the present study was that in the current study was found to be most resistance to Nalidixic acid (59.7%).…”
Section: Discussionsupporting
confidence: 83%
“…followed by P. aeruginosa. 32 Though only 1% strains causing tracheal infection were Enterobacter spp. in our study, those were multidrug resistant.…”
Section: Xdr 22%mentioning
confidence: 99%
“…5 Again due to irrational use of antibiotics, there is increasing emergence of drug-resistant bacteria. 6 These gram-negative drug resistant bacteria are prevalent all over the world. 7 The aim of our study was to detect different pathogens from endotracheal aspirate in ICU patients and to see their antimicrobial susceptibility pattern.…”
Section: Introductionmentioning
confidence: 99%